PENGARUH KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT. VEGAS VIVA VENTURY DENPASAR - Ni Putu Devi Ariananda Putri; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
Human resources in this case are employees who are social creatures who are the main assets in a company that must be paid attention to, because human resources are the main players in a company. The aim of this research is to determine the effect that job satisfaction can mediate on compensation's influence on turnover at PT. Vegas Viva Ventury. This research was conducted at PT. Vegas Viva Ventury. PT. Vegas Viva Ventury Bali which is located at Jalan Hayam Wuruk No. 211 Sumerta Klod, East Denpasar District. The objects of this research are Compensation, Employee Turnover Intention and Job Satisfaction. Population of PT employees. Vegas Viva Venture as many as 67 people. In this research sample, the population and saturation taken were all employees of PT. Vegas Viva Ventury as many as 67 people. In this research, the Partial Least Square (PLS) approach was used. The research results show that compensation has a positive effect on job satisfaction. Job satisfaction has a negative effect on turnover intention. Compensation has a negative effect on turnover intention. Compensation has an effect on turnover intention after being mediated by job satisfaction.